Воля судьбы: [роман] / Михаил Волконский - Волконский Михаил Николаевич (Романы князя Волконского, 2009)
Экземпляры: ф.15 (20151217) / Инвентарный номер: 47570 / Цена: 80.00 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: В 67 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1